Enhancing High School Students’ Basic Programming Skills and Self-Efficacy: A Drill-and-Practice Game-Based Approach - Isnania Lestari; Ferry Marlianto; Dewi Sulistiyarini; Febrianto Sabirin; Noorjima Abd Wahab (FKIP Universitas Lampung, 2026)
Drill-and-practice educational games combine repetitive practice with gamification through rewards, achievements, challenges, feedback, and progress tracking to support gradual skill development. In this study, the drill-and-practice element focuses on repeated, structured practice of basic programming exercises with immediate corrective feedback and multiple attempts until mastery. This study examined the effect of a drill-and-practice educational game on basic programming skills and programming self-efficacy among senior high school students. This quasi-experimental study used a Non-Equivalent Control Group Design. The sample comprised 179 tenth-grade students from six intact classes, selected via cluster random sampling. Three classes constituted the control group, with 89 students, and three classes constituted the experimental group, with 90 students. Students completed a basic programming pretest and posttest, as well as a self-efficacy questionnaire. Data were analyzed using descriptive statistics and MANCOVA with pretest scores as covariates. Descriptively, students’ overall basic programming scores increased from a mean of 38.70 to 70.49 in the posttest, while self-efficacy increased from a mean of 59.82 to 74.05. The multivariate test showed a significant group effect (Pillai’s Trace = 0.528; F = 97.442; p < 0.001; Partial η² = 0.528). Between-subjects tests indicated significant improvements in basic programming skills (F = 115.102; p < 0.001; Partial η² = 0.397) and self-efficacy (F = 86.697; p < 0.001; Partial η² = 0.331), with the experimental group achieving higher posttest outcomes than the control group. A drill-and-practice educational game can enhance both cognitive outcomes in basic programming and affective outcomes in self-efficacy, and can be considered an interactive learning alternative for programming topics at the high school level. Future studies should add performance-based coding tasks and broader samples to validate and extend these results. Keywords: educational games, drill and practice, basic programming skills, self-efficacy.